A Chandra and ALMA study of X-ray-irradiated gas in the central ∼100 pc of the Circinus galaxy. (25th June 2019) - Kawamuro, Taiki; Izumi, Takuma; Imanishi, Masatoshi
Abstract: We report on a study of X-ray-irradiated gas in the central ∼100 pc of the Circinus galaxy, which hosts a Compton-thick active galactic nucleus (AGN), at 10 pc resolution using Chandra and ALMA. Based on ∼200 ks Chandra/ACIS-S data, we created an image of the Fe Kα line at 6.4 keV, tracing X-ray-irradiated dense gas. The ALMA data in Bands 6 (∼270 GHz) and 7 (∼350 GHz) cover five molecular lines: CO( J = 3–2), HCN( J = 3–2), HCN( J = 4–3), HCO + ( J = 3–2), and HCO + ( J = 4–3). The detailed spatial distribution of dense molecular gas was revealed, and compared to the iron line image. The molecular gas emission appeared faint in regions with bright iron emission. Motivated by this, we quantitatively discuss the possibility that the molecular gas is efficiently dissociated by AGN X-ray irradiation (i.e., creating an X-ray-dominated region). Based on a non-local thermodynamic equilibrium model, we constrained the molecular gas densities and found that they are as low as interpreted by X-ray dissociation. Furthermore, judging from inactive star formation reported in the literature, we suggest that the X-ray emission has the potential to suppress star formation, particularly in the proximity of the AGN.